Platelet-rich plasma induces post-natal maturation of immature articular cartilage and correlates with LOXL1 activation - Cathy Thornton (Scientific Reports, 2017)
Platelet-rich plasma (PRP) is used to stimulate the repair of acute and chronic cartilage damage even though there is no definitive evidence of how this is achieved. Chondrocytes in injured and diseased situations frequently re express phenotypic biomarkers of immature cartilage so tissue maturation is a potential pathway for restoration of normal structure and function. We used an in vitro model of growth factorinduced maturation to perform a comparative study in order to determine whether PRP can also induce this specific form of remodeling that is characterised by increased cellular proliferation and tissue stiffness. Gene expression patterns specific for maturation were mimicked in PRP treated cartilage, with chondromodulin, collagen types II/X downregulated, deiodinase II and netrin1 upregulated. PRP increased cartilage surface cell density 1.5fold (P < 0.05), confirmed by bromodeoxyuridine incorporation and proportionate increases in proliferating cell nuclear antigen gene expression. Atomic force microscopy analysis of PRP and growth factor treated cartilage gave a 5fold increase in stiffness correlating with a 10fold upregulation of lysyl oxidase like1 gene expression (P < 0.001). These data show PRP induces key aspects of postnatal maturation in immature cartilage and provides the basis to evaluate a new biological rationale for its activity when used clinically to initiate joint repair.